Capital Budgeting Sophistication and - Peek, Johannes Samuel (My University, 2011)
The academic community has tried to convince corporate business managers that the capital budgeting decision-making process can be made more effective by using more sophisticated capital budgeting techniques. There are different capital budgeting tools and techniques available. The question that needs to be answered is whether using sophisticated capital budgeting techniques will give business a competitive edge? The study investigates the relationship between a firm’s capital budgeting sophistication and its long term operating performance. The study firstly investigates the use of different capital budgeting techniques. Using this information, a capital budgeting sophistication score is calculated. Secondly, financial information of the firm is used to calculate the firm’s average operating rate of return for the firm, relative to the average operating rate of return for the industry. The study takes into account firm size, capital intensity, operating risk and the degree of focus. Thirdly, the capital budgeting sophistication of companies and operating performance are compared to investigate a possible statistical relationship. It is concluded that there is a statistically significant, positive relationship between the degree of capital budgeting sophistication of a company and its operating performance. It would therefore be beneficial to industry to increase capital budgeting sophistication. This would lead to increase in return to shareholders, increasing the value of the company
MBA - WBS
Keywords: Budgets; Capital budgeting